2006
DOI: 10.1096/fj.05-5465com
|View full text |Cite
|
Sign up to set email alerts
|

The neuronal chemokine CX3CL1/fractalkine selectively recruits NK cells that modify experimental autoimmune encephalomyelitis within the central nervous system

Abstract: Leukocyte trafficking to the central nervous system (CNS), regulated in part by chemokines, determines severity of the demyelinating diseases multiple sclerosis (MS) and experimental autoimmune encephalomyelitis (EAE). To examine chemokine receptor CX3CR1 in EAE, we studied CX3CR1(GFP/GFP) mice, in which CX3CR1 targeting by insertion of Green Fluorescent Protein (GFP) allowed tracking of CX3CR1+ cells in CX3CR1(+/GFP) animals and cells destined to express CX3CR1 in CX3CR1(GFP/GFP) knockouts. NK cells were mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
259
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 263 publications
(276 citation statements)
references
References 56 publications
15
259
2
Order By: Relevance
“…EAE in CX3CR1 Ϫ/Ϫ mice showed exaggerated disease severity, associated with an impairment of the migration of regulatory NK cells to the CNS. 88 These results, and corollary studies, suggest a protective role of NK cells during EAE, and showed further that CX3CL1-CX3CR1 govern the migration of these cells to the CNS, but not to the liver.…”
Section: Multiple Sclerosis: a Jumble Of Chemokines And Chemokine Recmentioning
confidence: 54%
“…EAE in CX3CR1 Ϫ/Ϫ mice showed exaggerated disease severity, associated with an impairment of the migration of regulatory NK cells to the CNS. 88 These results, and corollary studies, suggest a protective role of NK cells during EAE, and showed further that CX3CL1-CX3CR1 govern the migration of these cells to the CNS, but not to the liver.…”
Section: Multiple Sclerosis: a Jumble Of Chemokines And Chemokine Recmentioning
confidence: 54%
“…It is proposed that microglia has a prominent role in mediating the neuroprotective effects of CX3CL1 (Mizuno et al, 2003;Huang et al, 2006;Cardona et al, 2006) and we have recently shown that CX3CL1-stimulated microglia releases neuroprotective substances that reduce Glu-induced cell death (Lauro et al, 2008). However CX3CL1 does not protect against all types of neuronal damage because in transient brain ischemia (Soriano et al, 2002;Dénes et al, 2008) and in a rat model of Parkinson's disease, intrastriatal CX3CL1 injection induced both microglia-dependent depletion of dopaminergic cells and motor dysfunction (Shan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…CX3CL1 is constitutively expressed in the nervous system, but levels in the brain can be modulated under diverse pathological conditions (Pan et al, 1997;Hughes et al, 2002;Kastenbauer et al, 2003;Sunnemark et al, 2005;Huang et al, 2006). The presence and the stimulation (Zujovic et al, 2000(Zujovic et al, , 2001Mizuno et al, 2003;Cardona et al, 2006;Lyons et al, 2009) of the CX3CL1 receptor CX3CR1 has been correlated with a reduced release of interleukin-1-b (IL-1-b) and tumor necrosis factor-a (TNF-a) from microglial cells and a lower rate of neuronal degeneration in different experimental models of neuropathologies such as experimental autoimmune encephalomyelitis, 1-methyl-4-phenyl-1,2,3,6 tetrahydropyridine hydrochloride striatal injection, lipopolysaccharide administration, and superoxide dismutase (SOD1) mutation (Huang et al, 2006;Cardona et al, 2006). These data attest to a role of the pair CX3CL1/CX3CR1 in reducing neuronal degeneration on several types of brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…Although neuroprotective functions of MSCs that have migrated to brain lesions are not fully understood, the temporal and spatial differences in the expression of chemokine receptors on hMSCs transplanted into the brains of prion-infected mice that we observed in the present study is intriguing, i.e., hMSCs that are considered to be in the process of migration in the corpus callosum expressed CCR3, CCR5, and CXCR3, whereas hMSCs that had migrated to the target site showed reduced expression of these receptors but elevated expression of CCR1 and CX3CR1. The stimulation of CX3CR1 by its ligand CX3CL1 plays a role in modulating the release of proinflammatory cytokines from microglia (7,21) and in producing neuroprotective substances (31). Therefore, the expression of CX3CR1 on MSCs that had migrated to the contralateral hippocampus might be an indicator of functional alteration of hMSCs, i.e., alteration from active migration toward the target site to exhibition of neuroprotective potential.…”
Section: Discussionmentioning
confidence: 99%